New Insights into the Interplay Between Simple Sugars and Liver Diseases - Simona Parisse; Erika Coltorti; Monica Mischitelli; Flaminia Ferri; Stefano Ginanni Corradini (Current Issues in Molecular Biology)
In hepatology, there is growing interest in identifying the mechanisms and risk factors underlying liver diseases with increasing incidence, with particular focus on metabolic dysfunction-associated steatotic liver disease (MASLD) and its complications. Simple sugars have been recognized as key contributors to liver injury and disease progression, not only in the context of MASLD but also beyond. As a result, numerous studies have aimed to elucidate their role in liver pathophysiology. Specifically, simple sugars have been associated with pivotal mechanisms involved in the onset of liver diseases, including inflammation, de novo lipogenesis, oxidative stress, insulin resistance, and dysbiosis with increased intestinal permeability. These mechanisms collectively contribute to a significant association between simple sugar intake and liver diseases of varying stages and severity. The scientific evidence available to date has not only clarified potential pathogenic mechanisms and clinical correlations but also led to the identification of potential therapeutic targets, encompassing both lifestyle interventions and molecular approaches. This review aims to provide a comprehensive analysis of the associations between simple sugar intake, liver injury, and liver diseases. To this end, we conducted an extensive review of the literature, selecting the most relevant and up-to-date studies on the topic.